KINERJA BAITUL MAAL WA AT-TAMWIL (BMT) MASLAHAH LIL UMMAH-PONDOK PESANTREN SIDOGIRI MENGGUNKAN BALANCE SCORECARD MODIFIKASIAN - Purnama Putra (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2015)
Pesantren (Islamic Boarding School) has a significant role in the development of the nation when it canoptimize its potential. Pesantren which can be considered as the miniature of a nation. It can be the agent of socialpiety by spreading the Islamic teaching on economy based on the fulfillment of sharia. BMT Maslahah Mursalah lilUmmah tries to prove that pesantren can apply the role in improving the life of the people around the pesantren.This research is aimed to measure the working performance of BMT MMU which is pesantren based using modifiedBalanced Scorecard and to find out the solution of the problem, also to show the best practice made by BMT MMUin developing Islamic Micro Financial Institution. The research design is parallel mixed method. The result showsthat the working performance of BMT MMU is in an excellent level. The most influential performance is economicempowerment and social legitimation. To solve several problems related to the development of BMT MMU, themanagement developed the quality of human resource and involved other people outside of the pesantren in itsoperational activities.